Immunogenicity of Inactivated SARS-CoV-2 Vaccines in Patients With Rheumatoid Arthritis: A Case Series - Ting Zhao; Ting Zhao; Jiayan Shen; Jiayan Shen; Youyang Zhu; Xiaofang Tian; Guangfen Wen; Yuanyuan Wei; Bonan Xu; Chenyang Fu; Zhaohu Xie; Yujiang Xi; et al. (Frontiers Media S.A., 2022)
ObjectivesAttenuated humoral response to mRNA SARS-CoV-2 vaccines has been reported in some patients with autoimmune disease, e.g., rheumatoid arthritis (RA). However, data of immune responses to inactivated SARS-CoV-2 vaccine in the RA population are still unknown. Herein, the safety and immunogenicity of inactivated SARS-CoV-2 vaccines in RA patients were analyzed.MethodsSeventy five RA patients and 26 healthy controls (HC) were respectively recruited from Yunnan Provincial Hospital of Traditional Chinese Medicine and the community in Kunming city. Neutralizing Antibody (NAb) Test ELISA kit was used to measure the percentage of inhibition. AKA (anti-keratin antibody) positivity was detected using indirect immunofluorescence. Rheumatoid factor (RF)-IgA was detected by ELISA. RF-IgG, RF-IgM, and anti-cyclic citrullinated peptide (CCP) antibodies were measured by chemiluminescence. ESR (erythrocyte sedimentation rate) was detected by ESR analyzer. C-RP (c-reactive protein) was detected by immunoturbidimetry. NEUT% (percentage of neutrophils) and LYMPH% (percentage of percentage) were calculated by a calculation method.ResultsCompared with the HC group, the percentage of inhibition was significantly lower in RA patients receiving two doses of vaccines. Vaccines-induced percentage of inhibition was the lowest in RA patients who had not been vaccinated. In total 80.77% of the HC group had a percentage of inhibition ≧20%, compared with 45.24% of vaccinated RA patients and 6.06% of unvaccinated RA patients. Spearman correlation analysis revealed that antibody responses to SARS-CoV-2 did not differ between RA patients according to their age and disease duration. Furthermore, the results showed that no correlation was found between the percentage of inhibition and indices for RA, including RF-IgA, IgG, IgM; anti-CCP antibody; ESR; C-RP; NEUT% and LYMPH%.ConclusionOur study showed inactivated vaccine-induced SARS-COV-2 antibody responses differ in RA patients and healthy subjects, emphasizing the importance of a third or fourth vaccination in RA patients.